Quasi-equicontinuous exponential families of generalized function C-semigroups in locally convex spaces - M. Kostic, S. Pilipovic, D. Velinov (Springer Nature Switzerland AG. Springer, 2019)
Our main goal in this paper is to investigate the quasi-equicontinuous exponential C-distribution semigroups and quasi-equicontinuous exponential C-ultradistribution semigroups in the setting of sequentially complete locally convex spaces. We contribute to previous work and the work of many other authors, providing additionally plenty of various examples and applications of obtained results.
Keywords: C-distributions semigroups, C-ultradistribution semigroups, Integrated C-semigroups, Convoluted C-semigroups, Well-posedness, Locally convex spaces